Análisis de la brecha de bienestar laboral entre trabajadores formales e informales: Un estudio para el caso de Loja–Ecuador en el año 2023 - Maza Massa, Elias Gustavo (2024)
The global analysis reveals that, on average, 74% of employed people report being satisfied with their work situation, a digit that increases to 77% in Latin America, thus highlighting significant regional differences in the perception of work well-being. In this sense, this research aims to evaluate the relationship between informality and labor well-being in the year 2023 in Loja, Ecuador, through econometric techniques, with the purpose of proposing public policy implications focused on the well-being of individuals. The data source used in this study is the UNL 2023-2025 research project survey, carried out in the canton of Loja, Ecuador, during the year 2023. The main results reveal that there is no statistically significant difference between well-being of formal and informal workers, despite the fact that formal workers have a higher average salary. The perception of job autonomy and improvement in physical health are associated with an increase in work well-being, regardless of the type of work performed. Finally, a well-being gap is not observed, given that there are no significant differences between the observable characteristics of both groups. Consequently, it is recommended to implement programs aimed at improving the quality of work that include both formal and informal workers, through initiatives that generate better affiliation to social security and labor protection.